On Kropina Change for mth Root Finsler Metrics - Peyghan, E.; Tabatabaeifar, T.; Tayebi, A. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study the Kropina change for mth root Finsler metrics and establish necessary and sufficient condition under which the Kropina change of an mth root Finsler metric is locally dually flat. Then we prove that the Kropina change of an mth root Finsler metric is locally projectively flat if and only if it is locally Minkowskian.